Tinjauan Teologis Terhadap Ritual Sumpah Tippu’sasa Dalam Adat Mentawai Di Desa Mongan Poula - Steven Eka Saputra Bungge; Maria Titik Windarti (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
Oaths play a crucial role in human life, particularly in religious and cultural aspects. This paper elucidates the concept of oaths as an endeavor to bolster the veracity of a statement by invoking sacred entities such as God. In Israeli culture, oaths are regarded seriously and involve the name of God, with the threat of divine punishment if the oath is breached. Challenges for Christians arise when they encounter the influences of local culture and traditions, such as the Tippu’ Sasa oath ritual of the Mentawai tribe, which contradicts biblical teachings. Therefore, a profound understanding of oaths and the challenges of maintaining the sanctity of the Christian faith amidst local culture becomes imperative. This underscores that oaths are not merely verbal acts but also reflect profound spiritual commitments, serving as the foundation for a meaningful and responsible life.